Audit of immediate outcomes for MCDA twins following laser therapy for twin–twin transfusion syndrome at the NSW Fetal Therapy Centre. (31st March 2016) - Wilson, Isabella; Henry, Amanda; Hinch, Ellen; Meriki, Neama; Challis, Daniel; Smoleniec, John; Welsh, Alec William
Abstract : Objective: To audit immediate pregnancy and neonatal outcomes of selective laser photocoagulation of communicating vessels (SLPCV) for twin–twin transfusion syndrome (TTTS) at the New South Wales Fetal Therapy Centre. Methods: Retrospective cohort study of 151 TTTS cases undergoing SLPCV between July 2003 and May 2013, evaluating procedural details, delivery and perinatal outcomes. Results: The majority of cases were Stage III at SLPCV (56.9%), although proportion of Stage II SLPCV increased over time ( P = 0.03). Survival to hospital discharge of at least one baby was 85.6% and dual survival was 52.5%. Median gestational age at delivery was 32.6 weeks (IQR 29.0–35.0 weeks) with a median of 11.4 weeks (IQR 8.3–14.7) from laser to delivery. Median birthweight was 1792 g (IQR 1288–2233 g), with 75% of babies admitted to the nursery, predominantly secondary to prematurity. Immediate SLPCV complications were in utero fetal demise <1 week postprocedure in 27 fetuses (19.6%) and/or ruptured membranes <1 week postprocedure in 9 fetuses (6.6%). Conclusions: This Australian series shows that local outcomes after SLPCV for stages II‐IV TTTS remain equal to the international published literature and have remained stable after an initial learning curve. Women were more likely to be Stage II rather than III in the more recent years. However, this does not appear to be attributable to altered referral patterns.